Impact of Maintenance Session Attendance and Early Weight Loss Goal Achievement on Weight Loss Success in a Community-Based Diabetes Prevention Program Intervention. Issue 4 (August 2021) - Napoleone, Jenna M.; Miller, Rachel G.; Devaraj, Susan M.; Rockette-Wagner, Bonny; Arena, Vincent C.; Venditti, Elizabeth M.; Kramer, Kaye; Strotmeyer, Elsa S.; Kriska, Andrea M.
Purpose: The purpose of this study was to examine how maintenance session attendance and 6-month weight loss (WL) goal achievement impacted 12-month 5% WL success in older adults participating in a community-based Diabetes Prevention Program (DPP) lifestyle intervention. Methods: Data were combined from 2 community trials that delivered the 12-month DPP-based Group Lifestyle Balance (GLB) to overweight/obese adults (mean age = 62 years, 76% women) with prediabetes and/or metabolic syndrome. Included participants (n = 238) attended ≥4 core sessions (months 0-6) and had complete data on maintenance attendance (≥4 of 6 sessions during months 7-12) and 6- and 12-month WL (5% WL goal, yes/no). Multivariate logistic regression was used to estimate the odds of 12-month 5% WL associated with maintenance attendance and 6-month WL. Associations between age (Medicare-eligible ≥65 vs <65 years) and WL and attendance were examined. Results: Both attending ≥4 maintenance sessions and meeting the 6-month 5% WL goal increased the odds of meeting the 12-month 5% WL goal. For those not meeting the 6-month WL goal, maintenance session attendance did not improve odds of 12-month WL success. Medicare-eligible adults ≥65 years were more likely to meet the 12-month WL goal (odds ratio = 3.03, 95% CI, 1.58-5.81) versus <65 years. Conclusions: The results of this study provide important information regarding participant attendance and WL for providers offering DPP-based lifestyle intervention programs across the country who are seeking Medicare reimbursement. Understanding Medicare reimbursement-defined success will allow these providers to focus on and develop strategies to enhance program effectiveness and sustainability.